Nickel-aluminium layered double hydroxide as an efficient adsorbent to selectively recover praseodymium and samarium from phosphogypsum leachate (2023)
This study aimed to synthesize a green powdered layered double hydroxide (LDH) based on nickel-aluminum (Ni–Al-LDH) to evaluate its efficiency in the removal of rare earth elements (REEs), Praseodymium (Pr3+) and Samarium (Sm3+), from synthetic effluents and real leachate using phosphogypsum as a secondary source of REEs. Several characterization techniques were employed to evaluate the physicochemical properties of Ni-Al-LDH adsorbent, such as specific surface area and porosity, functional surface groups and phases, and point of zero charge. The characterization results indicated that Ni-Al-LDH exhibited a typical layered structure confirming the successful synthesis. The effect of key adsorption variables, such as pH, contact time, initial concentration, and temperature, on the REEs adsorption was extensively studied in single-factor experiments separately. The kinetic and equilibrium adsorption data agreeably fitted the Avrami and Sips models, respectively. The maximum adsorption capacities for Pr3+ and Sm3+ adsorption were 18.13 and 15.68 mg g−1 at 298 K, respectively. The thermodynamic parameters (ΔH0, ΔS0, ΔG0) indicated that the adsorption was spontaneous, favorable, and exothermic for both Pr3+ and Sm3+. The interactions between Pr3+ and Sm3+ onto Ni-Al-LDH suggest that multiple adsorption mechanisms are involved, such as ion exchange, precipitation, chelation, and pore filling. Finally, the Ni-Al-LDH could selectively recover REEs, specially Pr3+ and Sm3+, from the real phosphogypsum leachate. It has been demonstrated that Ni-Al-LDH is a promising adsorbent material that could be used as an adsorbent for the recovery of REEs from synthetic and real effluents.